Pengaruh Penggunaan Media Kartu Angka Terhadap Kemampuan Mengenal Lambang Bilangan Pada Anak Kelompok A - Agustina Ernawati; Baik Nilawati Astini; Ika Rachmayani; Fahruddin Fahruddin (Indonesian Journal of Elementary and Childhood Education, 2022)
This study aims to determine the effect of the number card game on the ability to recognize number symbols in group A children in Kindergarten, Langgudu District, Bima Regency, in the 2021/2022 academic year. This study uses a quantitative experimental pre-experimental design method with a one-group pretest-posttest design. The sample in this study was group A children in TK Langgudu District, a total of 24 people consisting of 13 boys and 11 girls. Sampling in this study used non-probability sampling with a purposive sampling technique. Data collection techniques in the form of observation and checklist. The analysis technique includes a normality test, hypothesis test and statistical hypothesis. The results of the normality test for the pretest value of 0.097 and the post-test value of 0.160 with a significance value > 0.05 which means that the pretest and post-test data are normally distributed. After the data is normally distributed, it is continued with hypothesis testing using paired sample t-test on the pretest and post-test values ??with sig. 2 tailed is 0.000 <0.05 with a t value of 59.98 > t table 1.711 which means that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. The value of Ha in question is that there is a difference between the pretest and post-test values ??so it can be concluded that "there is a significant influence from the use of number card media on the ability to recognize number symbols of group A children in TK Langgudu District in 2022.